Batch adsorption of an anionic dye from aqueous solution onto acid and basic activated carbon synthesized from almond shell by chemical activation method - Sediri, Meriem; Kerchich, Yacine; Cherifi, Hakima; Shamshuddin, MD. (Edelweiss Applied Science and Technology, 2025)
The aim of this study is to assess the impact of activating agents on the removal of methyl orange (an anionic dye) through the adsorption process in a batch system, utilizing acid and basic-activated carbons derived from almond shell grains. The acid and basic activated carbons (AAC and BAC) were prepared via chemical activation using phosphoric acid (H3PO4) and potassium hydroxide (KOH), respectively. Both types exhibited a high yield in adsorption capacity. The investigation into the effect of various operational parameters on adsorption capacity involved varying time, pH, temperature, and the amount of activated carbon. The results from the adsorption kinetics revealed that the equilibrium time is 40 minutes for both types of carbons. Additionally, at a temperature of 25°C, using 0.2 g of activated carbon, at pH 2 for AAC and pH 6 for BAC, the maximum adsorption efficiencies were 90% and 85%, respectively. The pseudo-first-order and pseudo-second-order kinetic models were applied to test the experimental data. The results showed that the dye uptake process onto acid-activated carbon followed the pseudo-second-order rate expression, and the uptake using basic-activated carbon followed the pseudo-first-order model. These results suggest that it is feasible to convert wastes into porous materials for the effective removal of dyes from aqueous environments.